The simplex regression model as a methodology of actuarial analysis - Cavalcante, Jaime Phasquinel Lopes (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
The risk management business evolves rapidly, so actuaries are faced with the need for new analysis methodologies. However, the use of incorrect methodologies for actuarial modeling can have serious implications for strategic decision making. This study aims to introduce the simplex regression model as a suitable methodology for actuarial modeling of data whose values belong to the unit interval. Using a risk management data set, the linear model with normal distribution and the proposed regression model were compared. The evaluation of the models presented concluded by the quality of the modeling through simplex regression, indicating the quality of this method as a new analysis tool for the actuarial context.